2003
DOI: 10.1088/0953-2048/16/9/305
|View full text |Cite
|
Sign up to set email alerts
|

Tensile damage and its influence on the critical current of Bi2223/Ag superconducting composite tape

Abstract: We have studied the tensile behaviour of Bi2223 superconducting composite tapes at room temperature, and the influence of the tensile damages introduced at room temperature on the critical current Ic and the n values at 77 K. In the measurement of the Ic and n values, the overall composite with a gauge length 60 mm was divided into six elements with a gauge length of 10 mm in order to find the correlation of the Ic and n values of the overall composite to those of the local elements which constitute the compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
73
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 29 publications
(52 reference statements)
2
73
0
Order By: Relevance
“…1, have been observed. 1,2) The extent of cracking varies along the tape length. Accordingly, when the sections S1 to S6 schematically shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1, have been observed. 1,2) The extent of cracking varies along the tape length. Accordingly, when the sections S1 to S6 schematically shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of the collective cracks observed in the sample used in this work has been observed also in other fabrication route Bi2223 tape. 1) It is also noted that the collective cracks are formed not only in Bi2223 tape but also in brittle filamentsductile matrix (stabilizer) composite tape such as Nb 3 Sn multi-filamentary conductor. 6) When V (voltage)I (current) curves are measured for many sections ( Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This behaviour is similar to the case under torsion strain [17] but different with the case under hard bending strain [16]. Further, this is different with the case in Bi-2223 tapes wherein the damage of the Bi-2223 filaments arose first locally in the weakest subsection, resulting in the reduction of the I c only in that subsection, even though the other subsections almost retained their original I c values [19].…”
Section: Resultsmentioning
confidence: 53%
“…Interestingly, it was observed that the value of the overall I c was similar with the damaged subsection. At higher strains, and after almost all filaments have been damaged in the weakest subsection, damage then propagated to neighboring filaments causing I c and n-value reduction [19,20].…”
Section: Introductionmentioning
confidence: 99%